The Cornerstone of Learning: the Role of Assessment in Education (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Assessment, far from being a mere test of knowledge, plays a pivotal role in the entire educational landscape. It's a continuous process that goes beyond assigning grades and serves as a compass for both teachers and students. This article delves into the multifaceted nature of assessment in education, exploring its impact on student learning, instructional strategies, and educational policies